Alternative forms of psychological interventions: Trauma and emotional expression - Mati , Katerina Alexandra (Homo Virtualis, 2025)
This study examines the subjective meaning-making of psychological trauma among young individuals, through the recollection of personal traumatic experiences, combined with the potential effectiveness of alternative forms of psychological interventions. The central aim of the research is an in-depth understanding of trauma as an experience that exceeds the individual’s adaptive capacities and often leads to emotional numbness. The theoretical framework draws on classic theories, such as those of Van der Kolk, Porges and others, focusing on how a traumatic event affects, among other things, both the formation of personality and the development of interpersonal relationships. The methodology combines literature review with innovative multimodal approaches, such as non-verbal expression through art, narrative and sand therapy, as well as the use of Appreciative Inquiry. The main findings indicate that trauma profoundly impacts memory, emotional regulation and the ability for interpersonal connection. Finally, reference is made to specific therapeutic methods, such as Eye Movement Desensitization and Reprocessing (EMDR) and Somatic Experiencing, which significantly contribute to trauma processing, transforming the traumatic experience into a starting point for personal reconstruction.